The Role of Genetic Testing in the Identification of Young Athletes with Inherited Primitive Cardiac Disorders at Risk of Exercise Sudden Death - Tiziano, Francesco Danilo; Palmieri, Vincenzo; Genuardi, Maurizio; Zeppilli, Paolo (Frontiers in Cardiovascular Medicine, 2016)
Although relatively rare, inherited primitive cardiac disorders (IPCD) in athletes have a deep social impact since they often present as sudden cardiac death (SCD) of young and otherwise healthy persons. The diagnosis of these conditions is likely underestimated due to the lack of shared clinical criteria and to the existence of several borderline clinical pictures. We will focus on the clinical and molecular diagnosis of the most common IPCDs, namely hypertrophic cardiomyopathies (HCM), long QT syndrome (LQTS), arrhythmogenic right ventricular cardiomyopathy (ARVC), and left ventricular non-compaction (LVNC). Collectively, these conditions account for the majority of SCD episodes in athletes and/or cardiologic clinical problems. In addition to the clinical and instrumental tools for the diagnosis of IPCD, the viral technological advances in genetic testing have facilitated the molecular confirmation of these conditions. However, genetic testing presents several issues: the limited sensitivity (globally, around 50%), the low prognostic predictive value, the probability to find pathogenic variants in different genes in the same patient, and the risk of non-interpretable results. In this review, we will analyze the pros and cons of the different clinical approaches for the pre-symptomatic identification, the diagnosis and management of IPCD athletes; we will discuss the indications to the genetic testing for patients and their relatives, particularly focusing on the most complex scenarios, such as pre-symptomatic tests, uncertain results, unexpected findings.